Doing Business in Europe Economic Integration Processes, Policies, and the Business Environment (Contributions to Management Science,, 2018)
The book brings together an international panel of experts on economic integration and international business to address the essential link between the two fields, namely the impact of integration processes on the business environment. Focusing on the European Union, it presents numerous examples and case studies to demonstrate how local business is becoming international business, and addresses the opportunities, constraints and overall historical changes. Starting with the regional and global economic integration framework, and subsequently exploring the institutional structure that makes everything possible and how the union came to be, the book reveals how the common policies of the EU impact businesses and entrepreneurship within both the common market and the member states. Readers will learn about the economic and political context that affect businesses in Europe; understand the basic concepts of integration, accompanied by cases and examples; gain a new perspective on important EU sectoral policies and challenges for individuals and businesses; become aware of the main challenges to EU enlargement; and better grasp the advantages and disadvantages of doing business in Europe in the present context. .